Parents perception on Comprehensive Sex Education (CSE) / Nur Adibah Damit and Nur Shatila Ahmadsah - Damit, Nur Adibah; Ahmadsah, Nur Shatila (2014)
The increasing of the social problems among teenagers alarming the public that this problem cannot be taken lightly and this is really worrying, especially among parents. Because of that, there were comes to the mind that Comprehensive Sex Education (CSE) might be suitable to minimize the social problems among teenagers in Malaysia. As parents is the closest person to the children, it is so important to seek the perception among parents towards the possibility of introducing CSE at schools by using the questionaire surveys. It is found that few of the respondents are pessimistic towards CSE, however, there are several interesting findings that have been discussed and highlighted which majority of respondents are optimistic towards CSE to be introduced at schools.. In summary, everything related with this study have been discussed.